Systematic review and meta-analysis of randomised trials to ascertain fatal gastrointestinal bleeding events attributable to preventive low-dose aspirin: No evidence of increased risk - Elwood P.C. (Public Library of Science, 2020)
10.1371/journal.pone.0166166